In vitro rapid multiplication of Stevia rebaudiana: an important natural sweetener herb - SHIVAJI DESHMUKH; RAVINDRA ADE (Nusantara Bioscience, 2012)
Abstract. Deshmukh S, Ade R. 2012. In vitro rapid multiplication of Stevia rebaudiana: an important natural sweetener herb. Nusantara Bioscience 4: 105-108. Stevia rebaudiana Bertoni, belonging to family Asteraceae and natural sweet plant, but due to poor seed viability, fertility, and vigor, Stevia cultivation is a challenging task. In the present study in vitro, rapid multiplication method was established for S. rebaudiana by inoculating explants on M.S. medium, supplemented with different combination of phytoharmone. The maximum number of shoots (18.3±0.8) was obtained on M.S. medium supplemented with BAP + KIN (1.5 + 0.5 mg/L). The highest rooting percentage (95.25) was observed with (IAA 0.1 mg/L). The rooted plants were successfully established firstly in soil with coco peat (1:1) and then directly in ordinary soil.